Answer:
choice B
Step-by-step explanation:
because the rest of the answer all have an input that have different outputs
Answer:
Step-by-step explanation:
x(x² + 2x + 4)-2((x² + 2x + 4)
x³+2x²+4x -2x²-4x-8
x³-8
Y= 0.26x+4.4*10^-4
Y= 0.26x+4.4*10,000
Y=0.26x+44,000
I'm not sure if you were only trying to simplify the problem, but I hope this helped
Answer:
The ordered pair to represent a in the equation a=2b+c if b=(6,3) and c=(-4,8) is: a=(8,14)
Step-by-step explanation:
b=(6,3)
c=(-4,8)
a=2b+c
Replacing b and c in the equation above:
a=2(6,3)+(-4,8)
Multiplying:
a=(2*6,2*3)+(-4,8)
a=(12,6)+(-4,8)
Adding:
a=(12+(-4),6+8)
a=(12-4,14)
a=(8,14)